-3(x-6)=-4+5

Simple and best practice solution for -3(x-6)=-4+5 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -3(x-6)=-4+5 equation:


Simplifying
-3(x + -6) = -4 + 5

Reorder the terms:
-3(-6 + x) = -4 + 5
(-6 * -3 + x * -3) = -4 + 5
(18 + -3x) = -4 + 5

Combine like terms: -4 + 5 = 1
18 + -3x = 1

Solving
18 + -3x = 1

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-18' to each side of the equation.
18 + -18 + -3x = 1 + -18

Combine like terms: 18 + -18 = 0
0 + -3x = 1 + -18
-3x = 1 + -18

Combine like terms: 1 + -18 = -17
-3x = -17

Divide each side by '-3'.
x = 5.666666667

Simplifying
x = 5.666666667

See similar equations:

| 9(y-3)=7+8y | | z^2-(3-2i)z+(5-i)=0 | | 13/6=-1 | | 80+55=x+51 | | (1-3y+8)=(2+6-4) | | 2x-3=3(x+9) | | 2[w-(4w+20)+12]=2(w+8) | | 9(k+1)-(-7k-7)=15k | | 80+55=53+x | | 6(x+-6)-8(x+2)=-10 | | 5(x)=(2x-2)(m+6) | | 2cosx-sinx=5/4 | | (X^2+9x-3)(X^2+6x-5)= | | 9-(4y-3)=2-5y | | 6x+13-4x+13=-6 | | 8x+3y=-33 | | 10x-2(2x-2)=5x+1 | | 2x/3-5=x/2-3 | | 4-5x=3x+20 | | ((7a^2b^3c^0)/(3a^3b^4c^3))^-4 | | (1-w)(5w-4)=0 | | 8(3w^2)= | | 16+5=1121 | | -7(v+2)+2v+5=8v+6 | | 16+5=921 | | x(7x-37)=30 | | 4t^2+3t+7= | | 13y+25=8y+5 | | 9x^2+18x+4y^2=27 | | 0.5*(c+2.8)-c=0.6c+0.3 | | 4[4-(5x-7)]=140x+212 | | -3x=3+2(x+1) |

Equations solver categories